Landmark research for pulses improvement - Singh, R. J.; Chung, G. H. (The Indian Journal of Genetics and Plant Breeding, 2017)
This chapter reports that pulse crops (rich in protein) and cereals (rich source of carbohydrate) are an excellent combination for balanced human diet. Crop rotation of legumes with cereals enriches the soil because legumes fix nitrogen in soil in a symbiotic association with Rhyzobium species. Pulse breeders have been confined to the primary gene pool (GP-1). Exploitation of secondary (GP-2) and tertiary (GP-3) gene pools for crop improvement is hampered because of pre and post-zygotic barriers. National and international research institutes have conducted extensive plant exploration to collect primitive cultivars, land races, and wild relatives before the spread of high yielding varieties and environmental destruction eliminates them. These invaluable materials are being deposited in medium and long-term storage of gene banks. Breeders have achieved substantial gain in the yield of pulse crops by conventional breeding by producing varieties that are resistant to abiotic and biotic stresses. Breeders have produced varieties with high protein content but without antinutritional elements. Roundup Ready 2 YieldÂ® soybean, produced through genetic transformation, has revolutionized the soybean production particularly in the United States. An example to exploit tertiary gene pool of soybean is shown. Such approach should be conducted for other legumes to broaden their genetic base.